POLITIK ISLAM MAHATHIR MOHAMMAD DI MALAYSIA DAN SOEHARTO DI INDONESIA - M. Zaki Mubarak; Mohamad Zaini Abu Bakar (UIN Raden Mas Said Surakarta, 2018)
This study explains the role and strategy of Malaysia during Mahathir Mohammad era and Indonesia in the Soeharto era in facing their Islamists group opposition. In their early period, these two regimes used an iron cage to defeat their political enemies. Mahathir fought with the power of PAS (Parti Al-Islam Se-Malaysia) which becomes more radical in the early of 1980s; meanwhile, Suharto faced the Islamic extremist groups in the early of 1970s. Mahathir consisted to give enough spaces for competition, Suharto did not want to compromise. In its progress, these two regimes chose softer strategy by playing 'Islamic cardsâ€™ due to the double purposes: coopting the opposite and building a better image as an Islamic regime. Hence, the political project of Islamization of Mahathir and Soeharto could not be separated from the problem of domestic political contestation and an effort to look for new legitimacy. Thereby, their Islamic political projects ended differently. Due to the monetary crisis and democratic reforms in 1998 affected the Soeharto regime to step down and make an end to all of the political projects he has designed. On the contrary, the Mahathir regime has successfully survived in facing the similar crisis, so that his pro-Islamic policy has passed off although not as aggressive as in the past.Â